PERFORMANCE AND CARCASSES COMPOSITION OF YOUNG PIGS FED RATION WITH PROBIOTIC SUPPLEMENTATION - I. M. S. P., Wibawa; Budaarsa, K.; Mahardika, I G. (Majalah Ilmiah Peternakan; Vol 22 No 2 (2019): Vol. 22 No.2 (2019), 2019)
This study aims at determining the performance and carcasses composition of young female pig which are reared intensively and fed good quality rations and probiotic supplementation Saccharomyces sp. This research was conducted at Experimental Laboratory, Faculty of Animal Science, Udayana University, Bukit, Jimbaran. The design using a randomized block design (RBD) with basic weighting grouping. This design is used randomly grouped in basic body weight. The bali pigs were allocated randomly into four treatments i.e. ration without additional probiotics (A), ration with 0.20% additional probiotics (B), ration with 0.25% additional probiotics (C), and ration with 0.30% additional probiotics (D). The treatments were conducted in 4 times replication so there are 16 pigs and kept in individual pens. The variables observed were the performance and composition of carcass. Based on the results, ration consumption, additional of body weight, FCR, digestibility rations and carcasses composition showed not significant differences. It can be concluded that the additional of probiotics in the ration of young female Bali pigs did not effect to the variable performance and carcass characteristic up to 0.30% addition level.